2018
DOI: 10.1016/j.redox.2018.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Protection against gamma-radiation injury by protein tyrosine phosphatase 1B

Abstract: Protein tyrosine phosphatase 1B (PTP1B) is widely expressed in mammalian tissues, in particular in immune cells, and plays a pleiotropic role in dephosphorylating many substrates. Moreover, PTP1B expression is enhanced in response to pro-inflammatory stimuli and to different cell stressors. Taking advantage of the use of mice deficient in PTP1B we have investigated the effect of γ-radiation in these animals and found enhanced lethality and decreased respiratory exchange ratio vs. the corresponding wild type an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Animals under analysis were maintained individually in Phenomaster Metabolic Cages (TSE Systems International Group) from day 33 to day 38 and the evaluation was done during day 35–38. Spontaneous physical movement, drink and food intake, respiratory exchange (O 2 and CO 2 ), weight and heat production were monitored as previously described 28 .…”
Section: Methodsmentioning
confidence: 99%
“…Animals under analysis were maintained individually in Phenomaster Metabolic Cages (TSE Systems International Group) from day 33 to day 38 and the evaluation was done during day 35–38. Spontaneous physical movement, drink and food intake, respiratory exchange (O 2 and CO 2 ), weight and heat production were monitored as previously described 28 .…”
Section: Methodsmentioning
confidence: 99%
“…Regarding the inflammatory process associated with cholestasis, our data show that PTP1B deficiency differentially enhances the activation and recruitment of macrophages in the liver after BDL. We and others have described that PTP1B is an important modulator of macrophages activation, restricting the time of the proinflammatory signaling cascades in response to TLR ligands or IFN [29,52,56,57]. In this context, the results of the present work are in agreement with these studies since after the BDL markers of resident macrophages and recruited monocytes (F4/80, CD68, MCP-1, Ly6C) were elevated in the liver of PTP1B −/− mice.…”
Section: Discussionmentioning
confidence: 99%
“…It also should be mentioned that although it has been demonstrated that after 6 weeks of differentiation in the liver of irradiated and transplanted mice, BM-derived Kupffer cells closely resemble to resident Kupffer cells [60], we cannot exclude that remnant PTP1B +/+ Kupffer cells in the liver might attenuate the inflammatory phenotype of BM KO →WT mice. It is also worth noting that due to the extreme sensitivity of PTP1B −/− mice to irradiation [29,57], we were unable to perform BM transplantation in these mice which might have shed light on the importance of PTP1B status in inflammatory versus non-inflammatory liver cells in fibrosis progression.…”
Section: Discussionmentioning
confidence: 99%
“…including spinal cord injury and radiation injury [45,46]. However, whether PTP1B participates in cerebral IR injury-induced neuroinflammation as well as its relevant cell types were poorly defined.…”
Section: Discussionmentioning
confidence: 99%